The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/0020764020918278
|View full text |Cite
|
Sign up to set email alerts
|

Supported employment programme for persons with severe mental disorders in India: A feasibility study

Abstract: Background: A number of persons with severe mental illnesses are unable to prepare for, find or keep a job due to factors linked to their illness as well as psychosocial issues. Aim: To test the feasibility of a supported employment programme to help persons with severe mental disorders obtain and sustain employment. Methods: A supported employment programme was developed for persons with severe mental disorders with components of (a) assessment of vocational potential, (b) vocational counselling, (c) networki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 18 publications
0
36
0
Order By: Relevance
“…The current hybrid model of supported employment approach included skilling clients to be job ready while not in active employment and facilitating job placements when they expressed readiness has shown success, and encouraged persons with ID to work in mainstream community settings. A similar hybrid model of 'train and place 'and 'place and train' as depicted in this paper has shown to be efficacious in providing vocational services to persons with severe mental illness in France and Quebec [14] Studies reports that employment helps in changing the status of the persons with disabilities across various domains such as reduced financial burden, improvement of quality of life and self-esteem, enhanced standard of living, alleviation of stigma in the community and reduced emotional burden with greater individual autonomy [4]. In addition, studies also shown that meaningful employment is associated with improvement of a range of skills including cognitive abilities, social skills, interpersonal skills and community integration [15,16].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…The current hybrid model of supported employment approach included skilling clients to be job ready while not in active employment and facilitating job placements when they expressed readiness has shown success, and encouraged persons with ID to work in mainstream community settings. A similar hybrid model of 'train and place 'and 'place and train' as depicted in this paper has shown to be efficacious in providing vocational services to persons with severe mental illness in France and Quebec [14] Studies reports that employment helps in changing the status of the persons with disabilities across various domains such as reduced financial burden, improvement of quality of life and self-esteem, enhanced standard of living, alleviation of stigma in the community and reduced emotional burden with greater individual autonomy [4]. In addition, studies also shown that meaningful employment is associated with improvement of a range of skills including cognitive abilities, social skills, interpersonal skills and community integration [15,16].…”
Section: Discussionmentioning
confidence: 89%
“…A feasibility study on supported employment of Persons with Severe Mental Disorders (PwSMD)in India showed that out of 63 PwSMDs who were part of the study, 32 (50.8%) were placed in competitive jobs, placement was actively attempted for 17 (27.0%) and 7 (11.1%) were referred for skill training. The study also reported that their disability scores reduced significantly and socio-occupational functioning significantly improved in those who were placed over a period of 6 months [4]. Studies have also reported the role of reasonable accommodation in sustaining employment for persons with disabilities [4,5], Rangarajan et al, n.d.) Studies have reported that persons with developmental disabilities have the lowest rate of labor force participation, relative to other disabilities [6].…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…To promote optimal levels of social and vocational functioning for individuals with mental illness, it is therefore vital to have a multidisciplinary approach between service providers and caregivers in a well-coordinated operationalisation of recovery that is also patient-centred (Escorpizo et al, 2011; Liberman et al, 2001). This approach had been practiced in a supported employment model developed in India which included joint-sessions with family members to discuss employment expectations and preferences with the client, and the study had shown promising outcomes (Jagannathan et al, 2020). Unlike in India, most vocational initiatives in Singapore, emphasise on working with the individuals to address their needs and employability, and with employers, and co-workers to improve the working environment.…”
Section: Introductionmentioning
confidence: 99%